Patients with biliary atresia have elevated direct/conjugated bilirubin levels shortly after birth - Harpavat, Sanjiv; Finegold, Milton J; Karpen, Saul J (Pediatrics (Evanston), 2011)
Healthy infants are thought to acquire biliary atresia (BA) in the first weeks of life. Because those diagnosed earlier have better outcomes, we were interested in determining the earliest time BA could be detected. We started by examining the immediate postnatal period, hypothesizing that newborns would not yet have acquired disease and still have normal direct/conjugated bilirubin (DB/CB) levels. Newborn DB/CB levels were obtained retrospectively from birth hospitals. Subjects with BA were born between 2007 and 2010 and cared for at Texas Children's Hospital. Those with BA splenic malformation syndrome or born prematurely were excluded. Control subjects were term newborns who later never developed neonatal liver disease. Of the 61 subjects with BA, 56% had newborn DB/CB levels measured. All DB/CB levels exceeded laboratory norms and rose over time. At 24 to 48 hours of life, subjects with BA had mean DB levels significantly higher than those of controls (1.4 ± 0.43 vs. 0.19 ± 0.075 mg/dL, P < .0001), even while their mean total bilirubin (TB) levels remained below phototherapy limits. Finally, despite the elevated DB/CB levels, the majority of patients (79%) had normal DB:TB ratios ≤ 0.2. Patients with BA have elevated DB/CB levels shortly after birth. To detect affected infants earlier and improve outcomes, the results suggest two possibilities: (1) screen all newborns for elevated DB/CB levels, rather than just those who appear jaundiced; and then (2) follow all newborns with elevated DB/CB levels, rather than just those with DB:TB ratios >0.2.